Career Paths of Nursing Professionals: A Study of Employment Mobility - Hiscott, Robert Dennis (Carleton University Press, 1998)
A comprehensive study of the nursing profession using data collected from over 1600 surveys. This is the first and only comprehensive labour market study of the largest group of nursing professionals in any one province in Canada. It explores the career paths of more than 1600 registered nurses and registered practical nurses, using survey data collected in 1992-1993, just as these front line caregivers faced the sea change wrought by governmental restructuring in Ontario hospitals. A "snapshot" of key labour force and market issues in the nursing field, the study provides important baseline data from which the impact of present and future public policy trends and changes can be monitored, reviewed, and researched. The dimensions studied here include recent demographic shifts, the various forms of employment mobility, levels of voluntarism, career interruption, and nurses' reasons for leaving the field. Each line of inquiry raises pressing questions about the professional lives of those who work most directly and dynamically with patients but whose careers are being altered, perhaps detrimentally, by reorganization in the Canadian health care system. --Publisher's description